The role of training in the improvement of employee efficiency in fast food sector and an application - Yıldız, Peyman (My University, 2008)
Günümüzdeki işletmeler, küreselleşme ve teknolojik gelişmeler sonucunda birçok değişim ve gelişimle karşı karşıya kalırlar. Bu yüzden, var olabilmek ve gelişebilmek için rekabet güçlerini arttırmak zorundadırlar. Rekabette başarılı olabilmek için, iyi eğitilmiş ve işletmelere iyi adapte olmuş çalışanlara ihtiyaçları vardır. Bunların yanı sıra, eğitim sürekli olmalıdır. Özetle, teknolojik ilerlemeler ve küreselleşme örgütlerde değişimlere sebep olmaktadır ve bu değişimlerle başa çıkabilmek için çalışanlarını sürekli eğitmek zorundadırlar. Etkinliği, Çalışanlar, Fast Food, Çalışan Etkinliği

Nowadays, organizations face with fast and rapid changes and improvements that happen because of globalization and technological changes. Therefore, they have to raise their competition power in order to exist and develop themselves. To be accomplished in competition, companies need workers who should be well trained and well adopted to their companies. Moreover, training process must gain continuity. To sum up, globalization and technological shifts lead to changes even in organizations. In order to cope with these changes, companies need to train their employees. Key Words: Effectiveness of Training, Workers, Fast Food, Employee Efficiency
Keywords: Çalışan Etkinliği; Eğitim Etkinliği